2008
DOI: 10.1155/2009/687259
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin and Male Fertility: The Long and Short Feedback Regulation

Abstract: In the last 20 years, a pituitary-hypothalamus tissue culture system with intact neural and portal connections has been developed in our lab and used to understand the feedback mechanisms that regulate the secretions of adenohypophyseal hormones and fertility of male rats. In the last decade, several in vivo rat models have also been developed in our lab with a view to substantiate the in vitro findings, in order to delineate the role of pituitary hormones in the regulation of fertility of male rats. These stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 71 publications
(79 reference statements)
7
29
1
Order By: Relevance
“…Moreover, reverse causation is always a potential concern for this type of studies. However, high PRL would be expected to lead to lower BPA level (Gill-Sharma, 2009;Takeuchi et al, 2006), an opposite relation to what we observed. Thus, our results are unlikely as a result of reverse causation.…”
Section: Hormone Parametercontrasting
confidence: 90%
“…Moreover, reverse causation is always a potential concern for this type of studies. However, high PRL would be expected to lead to lower BPA level (Gill-Sharma, 2009;Takeuchi et al, 2006), an opposite relation to what we observed. Thus, our results are unlikely as a result of reverse causation.…”
Section: Hormone Parametercontrasting
confidence: 90%
“…95 Although prolactin has no specific target organ in men, it seems to have a number of nonspecific actions, including control of testosterone secretion 96 and control of sexual behaviour and activity. 97 Expression of prolactin receptors on the choroid plexuses and the hypothalamus suggests a latent role for prolactin in the regulation of male fertility.…”
Section: Prolactinmentioning
confidence: 99%
“…Results concerning FSH hormone indicate the increase of the hormone level in blood sera of groups treated with high concentrations of the drug in comparison with may be attributed to the glucocorticoid drugs which reduce the hormone batches which release hormone GnRH secreted from hypothalamus gland [21].…”
Section: Figure (1): Mean ± Standard Deviationmentioning
confidence: 98%
“…regulated and have a role One of the factors that deter creating of Prolactin creating testosterone ; then these cells deter Prolactin while Estrogen hormone is considered a Prolactin stimulating agent . Relation between Prolactin and Testosterone is almost an inverse relationship , as the increase in Prolactin level is associated with the decrease of Testosterone in mature males [21].…”
Section: Figure (1): Mean ± Standard Deviationmentioning
confidence: 99%